Linking plant functional genes to rhizosphere microbes: a review. Issue 5 (21st November 2022) - Liu, Qi; Cheng, Lang; Nian, Hai; Jin, Jian; Lian, Tengxiang
Summary: The importance of rhizomicrobiome in plant development, nutrition acquisition and stress tolerance is unquestionable. Relevant plant genes corresponding to the above functions also regulate rhizomicrobiome construction. Deciphering the molecular regulatory network of plant‐microbe interactions could substantially contribute to improving crop yield and quality. Here, the plant gene‐related nutrient uptake, biotic and abiotic stress resistance, which may influence the composition and function of microbial communities, are discussed in this review. In turn, the influence of microbes on the expression of functional plant genes, and thereby plant growth and immunity, is also reviewed. Moreover, we have specifically paid attention to techniques and methods used to link plant functional genes and rhizomicrobiome. Finally, we propose to further explore the molecular mechanisms and signalling pathways of microbe‐host gene interactions, which could potentially be used for managing plant health in agricultural systems.